The in-servitude of Writing in the Age of Technique: Heidegger, Nietzsche, Benjamin and Foucault - Jordana Lluch, Ester (Re-presentaciones: Periodismo, comunicación y sociedad, 2021)
This article examines the relationships between writing, technique and thinking. Martin Heidegger’s reflections on why "science don’t think" allow us to examine the problem of the homogenization of thought and writing in contemporary universities. To indicate today that «academy don’t think» invites us to reflect on these prevailing modes of thought and writing. Following the links that Heidegger establishes between the compromise of the technique and the transformation of the writing we analyze his notion of serenity to oppose it to the way in which Friedrich Nietzsche, Walter Benjamin and Michel Foucault use different technical objects to generate new ways of thinking and writing.
Keywords: Thinking; Writing; Heidegger; Nietzsche; Benjamin; Foucault